Physicochemical Characteristics of Dry Noodles Substitution with Barracuda Fish (Sphyraena jello) and Flour - Adela Melati Thohiroh Ajima; Isnaini Rahmadi; Wildan Suhartini (Jurnal Teknologi Hasil Pertanian, 2024)
Protein consumption in Indonesia is relatively low. A person has a risk of health problems if they consume less protein. The protein content of barracuda fish meat is 20.45%, making it suitable to be the main ingredient of dry noodle products. The noodle's chewy texture, delicious taste, and affordable price make noodles a popular alternative to rice in Indonesia. In addition, the potential for barracuda fish in Indonesia in 2021 is 37.794,63 tons and in Lampung Province is 199,65 tons. The purpose of this study is to determine the effect of fortification levels of barracuda fish on yield, swellability, and chemical composition of dry noodles. Dry noodles formulation with the ratio of barracuda fish: wheat flour of 0:100, 10:90; 12,5: 87,5; 15:85; and 17,5:82,5. The analysis of dry noodles includes yield test, swellability, water content, fat, protein, ash, acid insoluble ash, and carbohydrates. The treatments were repeated two periods as replications. The result of this study showed that barracuda fish meat substitution has significant influences on yield, water content, fat content, protein content, ash content, acid insoluble ash content, and carbohydrate content of dry noodles. The best results were obtained at the composition level of barracuda fish and wheat flour of 15:85 with yield characteristics of 64,90%, swelling power of 104,17%, moisture content of 12,46%, fat content of 1,46%; protein content of 13,80%; ash content of 2,04%; acid insoluble ash content of 0.01%; carbohydrate content of 70,22%.